2018
DOI: 10.3389/fgene.2018.00601
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Interruptions Modify Age at Onset in Myotonic Dystrophy Type 1 by Stabilizing DMPK Expansions in Somatic Cells

Abstract: CTG expansions in DMPK gene, causing myotonic dystrophy type 1 (DM1), are characterized by pronounced somatic instability. A large proportion of variability of somatic instability is explained by expansion size and patient’s age at sampling, while individual-specific differences are attributed to additional factors. The age at onset is extremely variable in DM1, and inversely correlates with the expansion size and individual-specific differences in somatic instability. Three to five percent of DM1 patients car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 44 publications
5
48
0
Order By: Relevance
“…[30][31][32][33] Variant repeat-mediated suppression of somatic instability in DM1 has also been observed and strongly associated with milder symptoms and later age at onset. 13,[18][19][20][21]34 Patients with DM1 experience a slow progression of muscle weakness and atrophy, initially involving the distal muscles of the extremities and later affecting the proximal musculature. Patients can develop dysphagia and respiratory muscle weakness, with an increased risk for weight loss and aspiration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32][33] Variant repeat-mediated suppression of somatic instability in DM1 has also been observed and strongly associated with milder symptoms and later age at onset. 13,[18][19][20][21]34 Patients with DM1 experience a slow progression of muscle weakness and atrophy, initially involving the distal muscles of the extremities and later affecting the proximal musculature. Patients can develop dysphagia and respiratory muscle weakness, with an increased risk for weight loss and aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 The attenuation of symptoms is hypothesized to result, at least in part, from a stabilizing effect of RI that reduces expansion-biased instability in somatic cells. 13,20,21 In this context, we set out to compare motor, neurocognitive, and behavioral outcome measures of participants with adult-onset DM1 with RIs matched to participants with DM1 with PRs, as well as comparison of both groups to participants unaffected by DM1.…”
mentioning
confidence: 99%
“…In other words, a loss of AGG interruption likely predisposes CGG repeat tracts to large-scale expansions (149,152). Generally, the stabilizing role of interruptions is common for expandable repeats and has been reported for GAA (153,154), CAG (38,128,129,(155)(156)(157)(158)(159)(160)(161)(162), CCTG (54,58,(163)(164)(165), and other repeats in somatic tissues, intergenerational transmission, and experimental systems.…”
Section: Relationship Between Repeat Size and Instabilitymentioning
confidence: 99%
“…Research over the last decade has shown that the variability in clinical phenotype and age of onset can be correlated to sequence interruptions in the CTG repeat [13,[16][17][18], as well as DNA methylation of the area surrounding the CTG repeat [19,20]. The hypermethylation of the DM1 locus was, at first, thought to only be present in patients with congenital onset DM1 (CDM1) [21]; however, studies have shown hypermethylation to also be present in patients with non-congenital DM1 [4,19,22] and particularly in patients with repeat interruptions [4,20].…”
Section: Introductionmentioning
confidence: 99%
“…Barbè et al [19] reported the hypermethylation of both upstream and downstream CpG sites, mainly in patients with maternal inheritance of the disease allele and only in patients with more than 600 CTG repeats, while Legarè et al [20] observed variability in the methylation of downstream, but not upstream, CpG sites. While repeat interruptions have been associated with later onset [16,17], lower levels of somatic instability [17,18], and a milder phenotype [18], the association of methylation with clinical features has been more unclear. Hypermethylation has been correlated with earlier disease onset [4,19], muscular and respiratory features [20], and longer CTG repeats [4,19,20] but also with lower levels of somatic instability [20].…”
Section: Introductionmentioning
confidence: 99%